Development and validation of a m6A -regulated prognostic signature in lung adenocarcinoma - Chen, Yaxin; Xia, Lei; Peng, Yuxuan; Wang, Gang; Bi, Liyun; Xiao, Xue; Li, Cui; Li, Weimin (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) is the most frequent subtype of lung cancer, with a 5-year survival rate of less than 20%. N6-methyladenosine (m6A) is the most prevalent RNA epigenetic modification in eukaryotic cells, and post-transcriptionally regulates gene expression and function by affecting RNA metabolism. The alterations of functionally important m6A sites have been previously shown to play vital roles in tumor initiation and progression, but little is known about the extent to which m6A-regulated genes play in prognostic performance for patients with LUAD. Here, we presented an overview of the m6A methylome in LUAD tissues using transcriptome-wide m6A methylation profiles and found that differentially methylated transcripts were significantly enriched in tumor-related processes, including immune response, angiogenesis, and cell-substrate adhesion. Joint analysis of m6A modification and gene expression suggested that 300 genes were regulated by m6A. Furthermore, we developed a m6A-regulated prognosis-associated signature (m6A-PPS) by performing a multi-step process. The m6A-PPS model, a 15-gene set, was qualified for prognosis prediction for LUAD patients. By regrouping the patients with this model, the OS of the high-risk group was shorter than that of the low-risk group across all datasets. Importantly, patients with high m6A-PPS scores respond better to immunotherapeutic. Our results provide a valuable resource for understanding the important role of epitranscriptomic modifications in the pathogenesis of LUAD and obtaining potential prognostic biomarkers.